Structure of Forest Vegetation of Garhwal Siwalik Hills between the Rivers Khoh and Ganges - Rajwar, G. S.; Gupta, Subodh K. (Indian Forester, 1992)
The vegetation of Garhwal Siwalik hills between the rivers Khoh and Ganges has been studied for various phytosociological parameters. The forests on sites 1 to 5 consisted of Holoptelea - Terminalia, Adina - Schleichera. Shorea - Mallotus, Bischofia - holoptelea and Acacia Dalbergia communities respectively. The total tree density and the hasal cover of the forests have heen compared with those of certain tropical and temperate forests of the world. These forests are the extension of Himalayan temperate forests.